Layer two compression for erroneous wireless. Issue 1 (January 2021) - Ilham, D N; Candra, R A; Hardisal,; Suherman, S; Budiansyah, A; Satria, E; Anugreni, F; Saputra, D S
Abstract: Wireless connection such as 802.11 and cellar networks is preferred for internet connections as its quick set up and mobility. However, radio propagations are prone to signal errors, noises and interferences. Even more powerful modulations and coding were developed; they do not change the nature of error sensitive in wireless link. When network link worsens, the available bandwidth decreases. This exerts problems for the user speed requirement. This paper examines layer two compressions on decreasing link quality. The 802.11 network simulations based on Bianchi model and Shannon theory show that compression technique on layer two increases throughput about 10.27%, although delay increases about two times.